Adsorption and corrosion inhibition characteristics of some organic molecules containing methoxy phenyl moiety on mild steel in hydrochloric acid solution. (June 2015) - Gurudatt, Doddahosuru M.; Mohana, Kikkeri N.; Tandon, Harmesh C.
Graphical abstract: Abstract: The influence of three newly synthesized molecules on the corrosion inhibition of mild steel in acid media is studied. From Tafel slopes, it is evident that the anodic reaction is more polarized. Impedance study reveals that the increase in R ct values can be attributed to the formation of a protective film and the decrease in C dl values is due to an increase in the thickness of the electrical double layer. Total energy, E HOMO and softness are in the order of 3-MPTT > 4-AMTT > 3-MAH and dipole moment, E LUMO, energy gap, ionization potential and hardness are in the order of 3-MPTT < 4-AMTT < 3-MAH.